Factors Influencing Repurchase Intention on Trendiness Products Nowadays - Edy Yulianto Putra; Ervin Setyawan Al Wen Jun; Fendy Cuandra (Forum Kerjasama Pendidikan Tinggi, 2026)
The influence of social media on consumer behavior is increasingly significant in the digital era. The purpose of this study was to determine the effect of social media marketing activities on Miniso brand repurchase intentions in Batam City. Method: Quantitative research using Partial Least Squares Structural Equation Modeling (PLS-SEM) analysis was conducted on 385 respondents. Results: The findings indicate that social media marketing activities have a significant positive effect on brand relationships, trust, and loyalty, which then increase repurchase intentions. Conclusion of the research is social media marketing activities are an important strategy to increase customer loyalty and repurchase intentions for trendy products.